Social protection programs for women in developing countries - Lisa A. Cameron (IZA World of Labor, 2014)
Women are more likely than men to work in the informal sector and to drop out of the labor force for a time, such as after childbirth, and to be impeded by social norms from working in the formal sector. This work pattern undermines productivity, increases women's vulnerability to income shocks, and impairs their ability to save for old age. Many developing countries have introduced social protection programs to protect poor people from social and economic risks, but despite women's often greater need, the programs are generally less accessible to them than to men.
Keywords: O15; J16; I38; 330; social protection; social assistance; social insurance; gender; developing countries; women